2008
DOI: 10.2215/cjn.04741107
|View full text |Cite
|
Sign up to set email alerts
|

Higher Strength Lanthanum Carbonate Provides Serum Phosphorus Control With a Low Tablet Burden and Is Preferred by Patients and Physicians

Abstract: Results: At the end of week 4, 54% of patients achieved serum phosphorus control at dosages <3000 mg/d administered as one tablet per meal. Among patients who entered cohort B, control rates of 25, 38, and 32% for patients who were randomly assigned to 3000, 3750, or 4500 mg/d lanthanum carbonate, respectively, were achieved, with no increase in adverse events. Patients and physicians reported significantly higher levels of satisfaction with reformulated lanthanum carbonate compared with previous phosphate bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 13 publications
(6 reference statements)
1
22
0
2
Order By: Relevance
“…The relationship between adherence and pill burden appeared to be nonlinear such that the greatest fall-off in adherence occurred in patients prescribed 12 or more phosphate binder pills per day. It has been shown that lower pill burden is also associated with greater patient satisfaction (20), and thus it seems prudent that patients should not be prescribed more than 12 phosphate binder pills daily. However, the current study only tested associations, and it is unclear if lower pill burden will translate into a higher adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between adherence and pill burden appeared to be nonlinear such that the greatest fall-off in adherence occurred in patients prescribed 12 or more phosphate binder pills per day. It has been shown that lower pill burden is also associated with greater patient satisfaction (20), and thus it seems prudent that patients should not be prescribed more than 12 phosphate binder pills daily. However, the current study only tested associations, and it is unclear if lower pill burden will translate into a higher adherence.…”
Section: Discussionmentioning
confidence: 99%
“…30 Studies have also reported improved satisfaction among patients with CKD stage 5 when switched from their existing phosphate binder to one with a lower pill burden. 34,35 Tenapanor, administered once or twice daily in milligram quantities, may provide a means to reduce pill burden and mass in patients with hyperphosphatemia, thereby improving adherence to treatment. As is the case with phosphate binders, patients took the study drug (tenapanor or placebo) with meals in our study.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 Lanthanumun diğer fosfat bağlayıcılara göre en önemli avantajı günlük alınan tablet miktarının azlığıdır. 55 En önemli dezavantajı ise yüksek tedavi maliyetidir. Bununla beraber lanthanum karbonatın uzun dönem güvenliği ile ilgili veriler de az olduğundan hastaların dikkatli takibi yapılmalıdır.…”
Section: -Kalsi̇yum İçermeyen Fosfat Bağlayicilar A) Sevelamer Hidrokunclassified